2022
DOI: 10.3389/fpubh.2022.832079
|View full text |Cite
|
Sign up to set email alerts
|

Association of Metals and Metalloids With Urinary Albumin/Creatinine Ratio: Evidence From a Cross-Sectional Study Among Elderly in Beijing

Abstract: BackgroundEnvironmental exposure to toxic elements contributes to the pathogenesis of chronic kidney disease (CKD). Few studies focus on the association of urinary metals and metalloids concentrations with the urinary albumin/creatinine ratio (UACR) among elderly, especially in areas and seasons with severe air pollution.ObjectiveWe aimed to evaluate the associations of urinary metals and metalloids concentration with UACR, which is an early and sensitive indicator of CKD.MethodWe conducted a cross-sectional s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…In another analysis of the same population, we found that essential and non-essential elements, including Zn, Sr, Cd, and element mixtures disturb glucose levels ( 28 ). Meanwhile, another parallel evidence shows urinary Cu concentration was strongly positively associated with urinary albumin/creatinine ratio, which was a sensitive indicator of chronic kidney disease (CKD) ( 27 ). The decreased renal function associated with elevated Cu concentrations was also observed in the three-wave repeated-measures study of 201 older adults ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another analysis of the same population, we found that essential and non-essential elements, including Zn, Sr, Cd, and element mixtures disturb glucose levels ( 28 ). Meanwhile, another parallel evidence shows urinary Cu concentration was strongly positively associated with urinary albumin/creatinine ratio, which was a sensitive indicator of chronic kidney disease (CKD) ( 27 ). The decreased renal function associated with elevated Cu concentrations was also observed in the three-wave repeated-measures study of 201 older adults ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…The study was conducted in communities distributed from south to north in Beijing, which experienced the highest levels of fine particulate matter during the last 20 years in China ( 26 ). Further details regarding the study setting and design as well as inclusion and exclusion criteria were previously mentioned ( 27 , 28 ). Eligible participants were the elderly (above 60 years or more) who lived in the local community for over 5 years.…”
Section: Methodsmentioning
confidence: 99%